Telecommunication 4.0 Reinvention of the Communication Network - Li, Zhengmao (Springer Singapore, 2018)
This book proposes for the first time the concept of communication 4.0, exploring its nature in detail, and offering predictions for the future development of the telecommunication industry. Based on an in-depth analysis of hierarchical communications requirements, it applies Maslow's Model to telecommunication and illustrates the model's five degrees.